Engineering Properties of Palm Oil Clinker Fine-Modified Asphaltic Concrete Mixtures - Nura Shehu Aliyu Yaro; Madzlan Napiah; Muslich Hartadi Sutanto; Aliyu Usman; Intan Kumalasari Mizwar; Aliyu Mani Umar (Journal of Engineering and Technological Sciences, 2022)
Palm oil clinker (POC) is a non-biodegradable palm mill by-product typically discarded in dumpsites. This study analyzed the performance of POC powder (POCF) as bitumen modifier in terms of conventional and engineering properties of bitumen and asphalt mixture. For the study, base bitumen of 60/70 penetration grade was utilized and different POCF dosages (0, 2, 4, 6, and 8% by weight of bitumen) were added. The base bitumen was effectively modified with POCF and then characterized. The conventional and engineering properties of the modified bitumen and asphalt mixtures were assessed. From the characterization results, the formation of Si-O crystalline structure and a new Si-OH functional group was identified. Furthermore, a meandering pattern was observed due to the modification of the base bitumen with POCF. Based on the conventional test results it was revealed that the addition of POCF to the base bitumen resulted in a stiffer blend compared to unmodified bitumen. The addition of POCF improved the modified mixtures’ Marshall stability relative to the unmodified mixtures. Analysis of variance (ANOVA) and regression modeling showed the influence and significance of POCF-MB, with R2 values of (95-99%). Finally, the 4-6% POCF dosage was found to be the optimum dosage, yielding the best performance in terms of the engineering properties evaluated.